Targeting Antibiotic Resistance. Issue 23 (22nd March 2016) - Chellat, Mathieu F.; Raguž, Luka; Riedl, Rainer
Abstract: Finding strategies against the development of antibiotic resistance is a major global challenge for the life sciences community and for public health. The past decades have seen a dramatic worldwide increase in human‐pathogenic bacteria that are resistant to one or multiple antibiotics. More and more infections caused by resistant microorganisms fail to respond to conventional treatment, and in some cases, even last‐resort antibiotics have lost their power. In addition, industry pipelines for the development of novel antibiotics have run dry over the past decades. A recent world health day by the World Health Organization titled "Combat drug resistance: no action today means no cure tomorrow" triggered an increase in research activity, and several promising strategies have been developed to restore treatment options against infections by resistant bacterial pathogens. Abstract : No action today, no cure tomorrow : The development and spread of antibiotic resistance is a global threat to public health. After decades of declining interest in the development of new therapies against infections caused by pathogenic bacteria, a revitalization of antibiotic research has recently taken place. Structure‐based and mechanism‐based approaches, as well as interventions at the genetic level, hold great promise for conquering antibiotic resistance.